Pengaruh Online Customer Review Dan Online Customer Rating Terhadap Keputusan Pembelian Melalui E-Commerce Di UIN Banten - Adam Farhanul M; Abu Bakar Sidik; Dhuhayatun Naziah; Wahyu Hidayat (KOLONI, 2023)
(shoppe, lazada, tokopedia, bukalapak, etc.). Moreover, there are also most people who don’t want to accept the risk of damage to the product. and some people also pay attention so that damage doesn’t occur, with that people can get this information by opening two features through ratings and reviews from other consumers. The purpose of this study was to analyze the effect of online customer reviews and online customer ratings partially on purchasing decisions through e-commerce features at UIN Banten. This research uses descriptive inferential analysis method technique. data collection techniques are used by distributing questionnaires. The results showed that online customer ratings and online customer reviews have a positive influence on purchasing decisions with e-commerce. Online customer reviews and online customer ratings show a relationship between these two variables and purchases of 0.859. The coefficient of determination shows that the online customer review of the purchasing decision variable is 0.187 or 18.7%, so it can be interpreted that online customer reviews influence purchasing decisions by 18.7% while the other is 81.3% which is influenced by other factors besides online customer reviews.  Keywords: online customer review, online customer rating, e-commerce